1979
DOI: 10.1007/bf02373833
|View full text |Cite
|
Sign up to set email alerts
|

Dental and cranial variation in living Indriidae

Abstract: ABSTRACT. Four species of Indriidae are extant in Madagascar. We have studied large samples of each of these to characterize dental and cranial variation, and to estimate the degree of sexual dimorphism in the dentition and cranium. Two dental fields are apparent, characterized by reduced variability: (1) a canine field centered on the upper canine and occluding caniniform lower premolar, and (2) a cheek tooth field centered on the second molars. No consistent pattern of sexual dimorphism was found in dental o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

1979
1979
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 19 publications
2
26
0
1
Order By: Relevance
“…Sakai (1981), analyzing regional differences in Urotrichus, concluded that the least size variability was found in M2, which agrees with the results of the present study. Similar findings in Tupaia have been reported by Kondo et al (1994), and in Indriidae (Primates) by Gingerich and Ryan (1979). An association between early formation and low morphological variability in M1 was noted by Gingerich (1974).…”
Section: Discussionsupporting
confidence: 83%
“…Sakai (1981), analyzing regional differences in Urotrichus, concluded that the least size variability was found in M2, which agrees with the results of the present study. Similar findings in Tupaia have been reported by Kondo et al (1994), and in Indriidae (Primates) by Gingerich and Ryan (1979). An association between early formation and low morphological variability in M1 was noted by Gingerich (1974).…”
Section: Discussionsupporting
confidence: 83%
“…The landmarks were subsequently digitized into a coordinate system using the tpsDIG (v 2.0) (Rohlf, 2004) software package. The lower first molar was chosen because it is the least variable along the molar tooth row in most primate and non-primate taxa and likely represents the single best tooth to study size distribution and variability in the fossil record (Gingerich, 1974(Gingerich, , 1979. The relative location of molar cusps (protoconid, metaconid, hypoconid, and entoconid), along with the intersection of the anterior extension of the cristid obliqua with the protolophid base, were chosen as landmarks to capture either the gross dimensions of major crushing areas (the talonid basin of the lower molar) or the relative position of shearing structures (Fig.…”
Section: Geometric Morphometric Investigation Of Shapementioning
confidence: 99%
“…Jolly 8 It is tempting to relate the lack of sexual dimorphism in lemurs, including the large extinct lemurs, to a legacy of monogamy. The problem is that polygamous lemurs also have no or reduced dimorphism, including those with visible, physical fighting between males over estrous females, such as the solitary aye-aye and the troop-living L. catta [57,104,105].…”
Section: Pair-bonding and Female Dominancementioning
confidence: 99%